Task knowledge model for triage decision-support - Halim, S.A. (2017)
The paper discusses the construction of the task knowledge model to support the development of a triage decision-support system. Knowledge rather than experience is predominant in the triage decision making. Since the triage decision making knowledge is complex, we resort to knowledge modelling to help in the systematisation of the knowledge. The paper concentrates on the modelling of the task knowledge model to back triage decision-support. We adopted the CommonKADS methodology as a basis of modelling and engineering the knowledge. The top-down modelling approach availed general task structures that could be reused and adapted to engineer the triage decision-support task knowledge model. Consequently, the resulting task model informs the engineering of the triage decision-support domain knowledge model. Copyright ©2013 SCITEPRESS.